2019
DOI: 10.1097/ccm.0000000000003847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telemonitoring of Critically Ill Emergency Department Patients Awaiting ICU Transfer*

Abstract: Objectives: Because of overcrowding and limited critical care resources, critically ill patients in the emergency department may spend hours to days awaiting transfer to the ICU. In these patients, often termed “ICU boarders,” delayed ICU transfer is associated with poor outcomes. We implemented an emergency department–based, electronic ICU monitoring system for ICU boarders. Our aim was to investigate the effect of this initiative on morbidity, mortality, and ICU usage. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Patient zip code was matched with 2018 Internal Revenue Service (IRS) tax return data to determine mean household income as a potential marker of disparities [ 16 ]. Zip code level income data is commonly used as a proxy for socioeconomic status [ 17 – 19 ]. IRS tax return data groups adjusted gross income into 5 categories and provides information on total number of returns and total amount of income per each category.…”
Section: Methodsmentioning
confidence: 99%
“…Patient zip code was matched with 2018 Internal Revenue Service (IRS) tax return data to determine mean household income as a potential marker of disparities [ 16 ]. Zip code level income data is commonly used as a proxy for socioeconomic status [ 17 – 19 ]. IRS tax return data groups adjusted gross income into 5 categories and provides information on total number of returns and total amount of income per each category.…”
Section: Methodsmentioning
confidence: 99%
“…In this system, ICU doctors could remotely monitor vital signs and conduct 2-way video communication with patients in the ED boarding. 15 Additional studies demonstrated associations with decreased length-of-stay and wait time without compromising quality of care or costs. 16 Yet, its use was limited by many barriers including cost of development, reimbursement, legal concerns, patient adoption, and technology challenges.…”
Section: Introductionmentioning
confidence: 99%
“…9 Prior to coronavirus disease 2019, telehealth was used for consultations (eg, telestroke), transfer decision-making, patient interviewing, triage, and telemonitoring. [10][11][12][13][14][15] One such example includes telehealth to enable virtual evaluation of ED patients boarding for the ICU in the ED or awaiting transfer to the ICU in another hospital. In this system, ICU doctors could remotely monitor vital signs and conduct 2-way video communication with patients in the ED boarding.…”
Section: Introductionmentioning
confidence: 99%
“…The shortage of intensive care unit (ICU) resources, including equipment and supplies for renal replacement therapy (RRT), is a critical problem in several countries 1 8 even before the COVID-19 pandemic, drawing attention to the limited capacity of resources in ICU settings worldwide 9 17 . The demand for ICU beds with RRT support (ICU-RRT) exceeding the available capacity is a crucial issue in Brazil, mainly in public hospitals, postponing ICU admission and the RRT initiation 6 and affecting outcomes, such as hospital length of stay and mortality 18 – 23 .…”
Section: Introductionmentioning
confidence: 99%